Implementation school well-being in Indonesian Schools: a systematic literature review - Suwarniti, Urip; Wuryandini, Endang; Muhtarom, Muhtarom (ARKA INSTITUTE, 2025)
This study aims to systematically review various research results related to the implementation of school well-being in Indonesian schools. This study uses the Systematic Literature Review (SLR) method on seven articles published between 2016 and 2024 and discusses the application of school well-being and its supporting aspects. The analysis was conducted through thematic synthesis to identify the forms of implementation, supporting factors, inhibiting factors, implementation strategies, and the contribution of school management. The results of the study show that school well-being has been implemented in various educational contexts and is influenced by a positive learning environment, social support from teachers and parents, and transparent and participatory school management. The main obstacles include academic pressure, limited facilities, and teachers' suboptimal understanding of the concept of student welfare. Effective strategies include strengthening communication between school members, balancing academic demands and psychosocial needs, and school policies that prioritize student well-being. Overall, school well-being is an important foundation for realizing healthy, inclusive education that is oriented toward student happiness.